Narrow-diameter implants versus regular-diameter implants for rehabilitation of the anterior region: a systematic review and meta-analysis - Cruz, R. S. [UNESP] (2021)
The aim of this systematic review and meta-analysis was to evaluate studies comparing implant survival rates, marginal bone loss (MBL), and mechanical and biological complication rates between narrow-diameter implants (NDIs) and regular-diameter implants (RDIs) used for oral rehabilitation in the anterior region. The review was conducted according to the PRISMA checklist. Two independent reviewers performed a comprehensive search of the PubMed/MEDLINE, Embase, Scopus, and Cochrane Library databases for studies published until May 2020. A total of 843 implants (484 NDIs and 359 RDIs) were included. No significant difference in implant survival rate (risk difference (RD) 0.01, 95% confidence interval (CI) −0.01 to 0.03; P = 0.34), MBL (standardised mean difference −0.51 mm, 95% CI −1.29 to 0.26 mm; P = 0.19), mechanical complications (RD 0.01, 95% CI −0.02 to 0.04; P = 0.40), or biological complications (RD 0.01, 95% CI −0.09 to 0.11; P = 0.85) was found between the implant groups. Within the limitations of this study, it is concluded that NDIs are an effective alternative to RDIs due to similar survival rates, MBL, and mechanical and biological complication rates. However, future studies are highly encouraged due to the small number of interventional studies on this topic.